Feeding behavior of lambs fed diets containing old man saltbush hay - Bezerra-Moreno, Greicy-Mitzi; Borba, Hirasilva; Leal-de-Araújo, Gherman G.; Alves-Cirne, Luis-Gabriel; Boaventura-Neto, Oscar; Alves-de-Moraes, Salete; Pinto-de-Carvalho, Gleidson-Giordano; de Lima-Júnior, Dorgival M.; dos-Santos-Pina, Douglas (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: We hypothesized that a diet with old man saltbush hay used as an alternative source of nutrients could partially replace the concentrate in the feeding of feedlot lambs. Objective: This study evaluated the behavior and performance of lambs fed diets containing increasing levels of old man saltbush hay plus concentrate. Methods: Twenty-four castrated Santa Inês lambs at approximately eight months of age (22 ± 1.97 kg) were confined in a randomized complete design and fed diets containing 30, 40, 50, and 60% (dry matter: DM) of old man saltbush hay. Results: The intake of DM and neutral detergent fiber was not affected (p>0.05) by the level of old man saltbush hay. Intake of mineral salt decreased (p<0.01) as the proportion of old man saltbush in the diet increased. Weight gain (kg) and feed efficiency worsened (p<0.05) with 40% inclusion of old man salt bush hay. The time spent on feeding and chewing increased (p<0.05), while idle time was reduced (p<0.01) with dietary inclusion of old man saltbush. Feed efficiency decreased (p<0.05) with the inclusion of old man saltbush. Conclusion: Dietary inclusion of old man saltbush affects the feeding behavior and performance of lambs in feedlot.